The Influence of Workload and Job Satisfaction on the Performance of Employees of Perumda Tirta Mangutama Badung District with Work Motivation as Mediation Variables - Sugita, I Made; Darmawan, Anak Agung Rai; Trisnayanthi, Ni Nyoman; Putra, I Bagus Udayana (Universitas Warmadewa, 2024)
Employee performance is not yet optimal, seen from the effectiveness of resolving complaints and grievances. Employee performance refers to individual work performance which is regulated based on standards or criteria set by an organization. The aim of this research is to analyze the influence of workload and job satisfaction on employee performance with work motivation as a mediating variable. The population in this study were all permanent employees of Perumda Tirta Mangutama, totaling 293. The sample was determined using the Slovin formula with the sampling technique used was proportional stratified random sampling, so that 75 respondents were obtained. The data analysis method used uses descriptive analysis and inferential analysis using Structural Equation Model-Partial Least Square (SEM-PLS). The research results show that workload has a positive and significant effect on employee performance. Workload has a positive and significant effect on work motivation. Work motivation has a positive and significant effect on employee performance. Job satisfaction has a positive and significant effect on employee performance. Job satisfaction has a positive and significant effect on work motivation. The mediating effect of work motivation shows that work motivation acts as a partial mediator on the influence of workload and job satisfaction on employee performance.